The Effect of Pluchea indica Less Leaves Extract Againts Biofilm of Enterococcus faecalis and Fusobacterium nucleatum In Vitro - Agni Febrina Pargaputri; Elly Munadziroh; Retno Indrawati (Denta Journal Kedokteran Gigi, 2017)
Background: Enterococcus faecalis and Fusobacterium nucleatum are the most common bacteria found in infected root canal teeth and most of them often caused failure in endodontic treatments. These bacteria can form biofilm which makes them more resistant against antibacterial agents. Biofilm formation also causes a decrease in antibiotics and antimicrobials sensitivity. Pluchea indica Less leaves is a species of plants that has several chemical properties. It consists of flavonoids and polyphenols which have benefits to inhibit biofilm formation. Because of its benefits, the extract of Pluchea indica Less leaves can be potentially developed as one of sterilization dressing in root canal teeth. Purpose: The aim of this study was to determine biofilm formation inhibition of Pluchea indica Less leaves extract against Enterococcus faecalis and Fusobacterium nucleatum. Materials and Methods: The dilution method was done first to show the Minimum Inhibitory Concentration (MIC) of the extract. The inhibition biolfilm formation was tested using microtitter plate assay by measuring the bacterial biofilm Optical Density (OD) from ELISA reader’s results and using autoagregation assay to show the inhibition of adherance bacteria. The Pluchea indica Less leaves extract concentration used for inhibition of biofilm formation were 100%, 50%, 25%, 12,5%, and 6,25%. Results: The result of biofilm formation inhibition showed that Pluchea indica Less leaves extract were able to inhibit Enterococcus faecalis and Fusobacterium nucleatum’ biofilm formation with strong moderate effect. The autoagregation assay showed a decrease in autoagregation percentation of Enterococcus faecalis and Fusobacterium nucleatum. Conclusions: Pluchea indica Less leaves extract has effect to inhibit biofilm formation of Enterococcus faecalis and Fusobacterium nucleatum.